Marketing Communication Strategy in Peer-to-Peer Lending for Indodana Online Loan Services to Appeal to Millennial Customers - Putra, Aditya Eka; Husada, Safaruddin; Fianto, Latif (Journal of Research on Business and Tourism, 2024)
The impact of the internet on financial technology, or fintech, is evident in the marketing of various goods, particularly online loans through peer-to-peer lending platforms. Indodana, by leveraging advancements in information technology, has actively developed a marketing communication strategy to appeal to the millennial generation. This research employs qualitative methods to evaluate the marketing communication strategy applied to Indodana's online loan products, focusing on how the company develops and implements this strategy to attract millennial customers. Information was collected through interviews, observations, literature reviews, and online searches involving informants, including members of the marketing team, online loan clients, and potential customers. Utilizing a seven-stage marketing communication approach, encompassing goal setting, objective establishment, message content creation, media selection, development of the promotional mix, budgeting, and evaluation, the study found that Indodana's marketing communication strategy is highly advantageous. The use of innovative information technology and online media channels effectively attracts customers and potential clients with clear and appealing content. Furthermore, addressing the uneven access to information technology is crucial to ensuring the continued accessibility of offline services.